Differentiated Instruction to Improve Learning Effectiveness in A Disruptive Era - Nisa, Zakiyatul; ‘Alaniah, Almas Sharfina; Adibah, Dawi Farah; Putri, Rokhmatul Khoiro Amin; Asrohah, Hanun; Zainiyati, Husniyatus Salamah (Jurnal Basicedu, 2023)
In the era of the industrial revolution 4.0, there was the spread of information, communication and spontaneity tools, which is called the era of digital disruption. Learning innovations that are oriented towards the interests and potential talents of students can be done by developing a differentiated learning strategy. Differentiation puts forward the concept that each individual has different interests, potentials and talents, for that the teacher's role must be able to coordinate and collaborate these differences with the right strategy. This study aims to explain the important role of differentiation learning in the era of disruption. The method used is library research. Through differentiation learning in the era of disruption, teachers are given the freedom to teach material through different media. As a result, students have the ability to find, solve and follow up on the problems given. This ability exists because students are trained to study independently or in groups without coercion and dependence from educators. An educator makes variations of methods and media in the learning process by adjustingadjust students' learning styles.